Extreme heat and paediatric emergency department visits in Southwestern Ontario. Issue 5 (16th November 2020) - Wilk, Piotr; Gunz, Anna; Maltby, Alana; Ravichakaravarthy, Tharsha; Clemens, Kristin K; Lavigne, Éric; Lim, Rodrick; Vicedo-Cabrera, Ana Maria
Abstract: Objective: The risk of adverse health events is expected to increase with hotter temperatures, particularly among the most vulnerable groups such as elderly persons and children. The objective of this study was to assess the association between extreme heat and daily emergency department visits among children (0 to 17 years) in Southwestern Ontario. Methods: We examined the average maximum temperature, relative humidity, and daily paediatric emergency department visits in June through August of 2002 to 2019. We reviewed emergency department visits from two academic hospitals. Daily meteorological data from the local weather station were obtained from Environment and Climate Change Canada. Results: Extreme heat, defined as the 99th percentile of the maximum temperature distribution, occurred at 33.1°C and was associated with an overall 22% increase in emergency department visits, compared to the reference temperature of 21°C. This association was mostly found between the second and fifth day after the exposure, suggesting a slightly delayed effect. The results of the sub-group analysis indicate that the risk of an emergency department visit due to infectious disease increases by 35% and the most pronounced association was noted in children aged 1 to 12 years. Conclusions: Extreme heat is associated with an increased incidence of emergency department visits in children. As temperatures continue to increase, strategies to mitigate heat-related health risks among children should be developed.